(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: To assess the current perception, experiences and satisfaction of patients with the role of community pharmacists. Methods: A questionnaire based cross sectional study entitled ‘Assessment of patient’s perception, experience and satisfaction with the role of community pharmacist was conducted on 148 participants of age 18. Questionnaire was developed, translated to local language and validated. The study was conducted only after getting approval from the Institutional Ethical Committee. The paper forms were distributed to customers coming to community pharmacists. Perception of roles, experience and satisfaction level with community pharmacy services were assessed using SPSS. Results: The assessment of awareness showed that 89.5% of the respondents have good perception about community pharmacist’s role. The level of satisfaction and experiences with community pharmacists were comparatively lower.78% participants had good experience, whereas nearly quarter of the participants had low satisfaction with services provided by community pharmacists. According to the experiences with community pharmacists, respondents agreed that community pharmacists are reliable source of drug information (68.2%) and important healthcare professional (89.2%).However; only 38.5% agreed that pharmacists took personal responsibility for resolving drug related problems they discover. Majority of the respondents were satisfied with the way community pharmacists labeled and delivered the medicine. Conclusion: The study indicated that respondents had positive perceptions towards most of the roles of a CP. However, the views on experiences and satisfaction with current pharmaceutical services were slightly negative. This shows their willingness to be provided with more services. In order to benefit patients, pharmacists must effectively utilize their role. There are shortcomings in professional practices by pharmacists.